Application of a novel surgical difficulty grading system during laparoscopic cholecystectomy. (24th November 2021) - Asai, Koji; Iwashita, Yukio; Ohyama, Tetsuji; Endo, Itaru; Hibi, Taizo; Umezawa, Akiko; Suzuki, Kenji; Watanabe, Manabu; Kurata, Masanao; Mori, Yasuhisa; Higashida, Masaharu; Kumamoto, Yusuke; et al.
Abstract: Background: Prevention of bile duct injury and vasculo‐biliary injury while performing laparoscopic cholecystectomy (LC) is an unsolved problem. Clarifying the surgical difficulty using intraoperative findings can greatly contribute to the pursuit of best practices for acute cholecystitis. In this study, multiple evaluators assessed surgical difficulty items in unedited videos and then constructed a proposed surgical difficulty grading. Methods: We previously assembled a library of typical video clips of the intraoperative findings for all LC surgical difficulty items in acute cholecystitis. Fifty‐one experts on LC assessed unedited surgical videos. Inter‐rater agreement was assessed by Fleiss's κ and Gwet's agreement coefficient (AC). Results: Except for one item ("edematous change"), κ or AC exceeded 0.5, so the typical videos were judged to be applicable. The conceivable surgical difficulty gradings were analyzed. According to the assessment of difficulty factors, we created a surgical difficulty grading system (agreement probability = 0.923, κ  = 0.712, 90% CI: 0.587‐0.837; AC2  = 0.870, 90% CI: 0.768‐0.972). Conclusion: The previously published video clip library and our novel surgical difficulty grading system should serve as a universal objective tool to assess surgical difficulty in LC. Abstract : Asai et al. established a novel surgical difficulty grading system for laparoscopic cholecystectomy based on 25 items adopted by international consensus among over 500 surgeons. This grading system, together with the previously published video clip library, should serve as a universal objective tool to assess surgical difficulty in laparoscopic cholecystectomy.